Time Series Analysis of 222Rn Gas Measurements Received from Osmaniye Region - Kamislioglu, Mirac; Kulahci, Fatih (Ieee, 2015)
In this study, time series analysis of the data was performed with Radon gas (Rn-222) data that measured at equal time interval for a year from East Anatolian Fault Zone near and Karatas-Osmaniye Fault Zone located near Osmaniye city. Investigation is of great significance of Rn-222 gas exchange in the soil for Rn-222 concentration changes is used earthquake prediction studies. Time series is an analysis method showing how it changes over time of interest size and this variable providing potential future value estimate correctly. Series trend was found by autocorrelation and time series analysis making that received from regularly Rn-222 data throughout the history of 01.01.2008-31.12.2008. The results were compared.
Osmaniye Bölgesinden Alinan 222Rn Gazi Ölçümlerinin Zaman Serisi Analizi
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: Time series; Autocorrelation; Rn-222 gas; Earthquake